2022
DOI: 10.1021/acsami.2c12894
|View full text |Cite
|
Sign up to set email alerts
|

Study of Synergistic Effects of Cu and Fe on P2-Type Na0.67MnO2 for High Performance Na-Ion Batteries

Abstract: P2-type Na 0.67 MnO 2 with a stable structure and an open framework can provide numerous channels for fast Na + de/intercalation, for which it is considered to be advantageous in application of the cathode material for Na-ion batteries. However, the complex phase transition occurring during cycling and the lattice distortion triggered by the Jahn−Teller effect severely restrict its development. Herein, the modified Na 0.67 MnO 2 with Cu or Fe single-element doping as well as Cu and Fe double-element doping was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…It can be observed that the potential deviation between peak-O1 and peak-R1 of Ovs & Mg-sub was smaller than that of Ovs, indicating less polarization and more reversibility of Ovs & Mg-sub. The peak-O2 and peak-R2 correspond to the phase transformation between P′2 and OP4, providing secondary capacity contribution . It is the reason why Ovs & Mg-sub has excellent specific capacity in the 2.0–4.0 V voltage range.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that the potential deviation between peak-O1 and peak-R1 of Ovs & Mg-sub was smaller than that of Ovs, indicating less polarization and more reversibility of Ovs & Mg-sub. The peak-O2 and peak-R2 correspond to the phase transformation between P′2 and OP4, providing secondary capacity contribution . It is the reason why Ovs & Mg-sub has excellent specific capacity in the 2.0–4.0 V voltage range.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Na 0.67 MnO 2 possesses a high specific discharge capacity, but it is easy to react with H 2 O and CO 2 in the air to generate surface impurities, resulting in layered structure instability and electrochemical performance decline. [82][83][84] In terms of elemental composition, it is the stronger alkalinity of sodium ion that leads to a weaker air stability for sodium ion electrode materials compared to lithium ion electrode materials. Compared with LiOH, NaOH is highly hydrophilic and can absorb large amounts of water.…”
Section: Factors Affecting the Air Stabilitymentioning
confidence: 99%
“…By doping small amounts of cationic or anionic atoms into the lattice of sodium ion batteries cathode materials, the air/water stability can be significantly improved. [82,88] This generally includes cationic dopants (Al, Mg, Ca, Ti, Nb, and B) and anionic dopants (F, Cl, and S). Among the above dopants, Al, Mg and Fe are considered to be the most promising elements due to their low cost.…”
Section: Tactics Of Enhancing the Air Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The severe Jahn–Teller effect associated with the six-coordinated high-spin Mn 3+ cations causes the transformation of the lattice structure from hexagonal (P2) to orthorhombic (P2′). ,, The P2–P2′ transformation induces large lattice strain and Na + /vacancy order, which reflects in reduced sodium cation mobility and relevant capacity fading and further leads to structural collapse during repeated sodiation/desodiation cycles. The most commonly adopted strategy to mitigate cooperative Jahn–Teller distortion, suppress P2–P2′ phase transformation, and enhance structural stability of the oxide and mobility of the Na + ion consists in the substitution of a proper amount (usually 0.05 < y < 0.2 ,,, ) of Mn 3+ Jahn–Teller centers with electrochemically inactive cations (such as Li + , Mg 2+ , Zn 2+ , Al 3+ ) or active cations (such as Fe 3+ , Co 3+ , Ni 2+/3+ , and Cu 2+ ), ,,, maintaining a single Na x Mn 1– y M y O 2 phase …”
Section: Introductionmentioning
confidence: 99%